Generation and Characterization of an Anti-diclazuril Monoclonal Antibody and Development of a Diagnostic Enzyme-Linked Immunosorbent Assay for Poultry - Shen, Hong; Li, Chao; Sun, Han; Chen, Wanqin; Chen, Bilian; Yi, Yu; Mei, Jianfeng; Zhang, Yanlu; Ying, Guoqing (Frontiers in Nutrition, 2022)
An anti-diclazuril monoclonal antibody (mAb) was developed for use in enzyme-linked immunosorbent assay (ELISA)-based detection of diclazuril with high sensitivity and specificity, which can be used to measure anti-coccidial drug residues. The anti-diclazuril mAb had a half-maximal inhibitory concentration of 0.449–0.517 ng/mL. The mAb cross-reactivity with toltrazuril, toltrazuril 18 sulfone, clozaril, monesin, madurmycin, and salinomycin was very minimal (<0.1%). The detection limit of the ELISA using this mAb was 0.10 ng/mL and the sensitivity was 0.05 ng/mL. A standard curve generated in the range of 0.05–16.2 ng/mL had a linear correlation coefficient value of ≥0.99. The average recoveries of diclazuril from chicken and duck samples ranged from 85.0% to 102.5%.Intra- and inter-assay coefficients of variation ranged from 5.9% to 8.5% and 9.2% to 12.6%, respectively. Using the International Immunogenetics Information System®, the VH domain of the mAb was found to be encoded by an IGHV3 family gene and had the following complementarity determining region (CDR) sequences: GFTFSRY (CDR1), SRGGS (CDR2), and GDDNYAFAY (CDR3). The VL domain was encoded by an IGKV1 family gene and had the following CDR sequences: KSSQSLLNSRTRKNYLA (CDR1), WASTRES (CDR2), and KQSYNLHT (CDR3). This study provides a method to generate anti-diclazuril mAbs and determine their variable region sequences. The diagnostic ELISA developed using this mAb may drive additional studies on the monitoring and detection of food and veterinary drug residues.